Encyclopedia of modern U.S. military weapons - Laur, Timothy M. frey50; Llanso, Steven L.; Boyne, Walter J., 1929- (New York : Berkley Books, 1998)
This encyclopedia covers, in on eexhaustively researched volume, the weapons, vehicles, equipment and systems that have served our nation in the past and present. It provides a sharp historical perspective for each weapon system.
At head of title: The Army times, Navy times, Air Force times.
Keywords: Military weapons -- Encyclopedias. -- United States; Military weapons -- History -- Encyclopedias. -- 20th century